2020
DOI: 10.3390/nano10101944
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bacteriophages in Nanotechnology

Abstract: Bacteriophages (phages for short) are viruses, which have bacteria as hosts. The single phage body virion, is a colloidal particle, often possessing a dipole moment. As such, phages were used as perfectly monodisperse systems to study various physicochemical phenomena (e.g., transport or sedimentation in complex fluids), or in the material science (e.g., as scaffolds). Nevertheless, phages also execute the life cycle to multiply and produce progeny virions. Upon completion of the life cycle of phages, the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 215 publications
(242 reference statements)
0
19
0
Order By: Relevance
“…Nanoscale materials based on self-assembly of proteins are used for various purposes, including the formation of structurally different shapes; the development of biosensors; the manufacture of optical, conductive, semiconductor, and magnetic nanoelectronics materials; as well as in gene and drug-delivery devices and vaccines [1][2][3]. Viruses, as a natural source of countless self-assembling proteins, are particularly widely studied and adapted for these purposes [4,5]. They come in a wide variety of shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale materials based on self-assembly of proteins are used for various purposes, including the formation of structurally different shapes; the development of biosensors; the manufacture of optical, conductive, semiconductor, and magnetic nanoelectronics materials; as well as in gene and drug-delivery devices and vaccines [1][2][3]. Viruses, as a natural source of countless self-assembling proteins, are particularly widely studied and adapted for these purposes [4,5]. They come in a wide variety of shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Phage-based plaque detection has the advantage of high sensitivity, but it is time consuming. With the advent of chemical biology, a type of organic–inorganic hybrid probe formed by phage coupling to nanomaterials has been developed, based on the chemical modification of phages and the assembly of metal nanoparticles with the modified phages [ 39 ]. The optical properties of nanomaterials can be used for rapid and sensitive detection.…”
Section: Signals From Nanomaterials Conjugated With Phagesmentioning
confidence: 99%
“…There are many other studies on this use of phages beyond the scope of this brief overview that are can be found in several recent review articles [ 129 , 134 , 142 , 143 ].…”
Section: Genetically Engineered Phages To Facilitate Tissue Constructionmentioning
confidence: 99%